Uji Padatan Tersuspensi Total (TSS) Pada Sampel Air Limbah Sawit Secara Gravimetri - M. Hapiz Hermansyah; Yunita Panca Putri; Andi Arif Setiawan; Syaiful Eddy; Jumingin Jumingin; Wahyu Saputra (Universitas PGRI Palembang, 2024)
Palm oil liquid waste is a pollutant that has the potential to cause negative effects on the environment. This industrial waste is known to cause pollution, especially in water bodies. Through analysis of the chemical composition of TSS, the type of solid material dissolved in liquid waste can be identified. Gravimetry is an examination of the amount of a substance by weighing the results of the precipitation reaction. This research aims to determine the amount of suspended solids in palm oil wastewater using the gravimetric method. Based on the analysis that has been carried out, the highest Total Suspended Solid (TSS) value was obtained for sample A, namely 15.274 mg/L, sample B, namely 58.2 mg/L and sample C 57.1 mg/L. So the results can be stated that the Total Suspended Solid (TSS) value in palm oil wastewater is still below the quality standards contained in the Minister of Environment Regulation No. 05 of 2014.